2022
DOI: 10.3390/nu14224933
|View full text |Cite
|
Sign up to set email alerts
|

Potential Benefits of Selenium Supplementation in Reducing Insulin Resistance in Patients with Cardiometabolic Diseases: A Systematic Review and Meta-Analysis

Abstract: Background: Selenium is a trace element that has been reported to be effective in regulating glucose and lipid metabolism. However, there is conflicting evidence from different clinical trials of selenium supplementation in treating cardiometabolic diseases (CMDs). Objective: This meta-analysis aimed to identify the effects of selenium supplementation on insulin resistance, glucose homeostasis, and lipid profiles in patients with CMDs. Methods: Randomized controlled trials (RCTs) of selenium supplementation fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Attention should be drawn to the fact that the dietary evaluation of selenium is considered a marker of limited sensitivity because the concentrations of this mineral vary with the soil, which translates into a great oscillation in the amounts present in foods [10,54]. Associated to this, the scarcity of information about the nutritional composition of selenium in foods produced in the several Brazilian geographic regions leads to the use of foreign tables, which implies in over or underestimation of the amount of this mineral [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attention should be drawn to the fact that the dietary evaluation of selenium is considered a marker of limited sensitivity because the concentrations of this mineral vary with the soil, which translates into a great oscillation in the amounts present in foods [10,54]. Associated to this, the scarcity of information about the nutritional composition of selenium in foods produced in the several Brazilian geographic regions leads to the use of foreign tables, which implies in over or underestimation of the amount of this mineral [28].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that Brazil nuts are the main food source of this trace element, which is also present in meat, foods of animal origin, vegetables, cereals and fruits [7][8][9]. The literature has demonstrated that this mineral presents antioxidant and anti-in ammatory actions, and also participates of the insulin metabolism, with an impact on the glycemic pro le and other aspects related to insulin action [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The recent surveys have focused mainly on the correlations between type 2 diabetes mellitus and selenium intake [ 29 , 34 , 80 83 ], its level in plasma or serum blood [ 31 , 37 , 84 86 ], and Se metabolic comorbidities [ 87 ], and metabolic syndrome [ 88 ]. The association of selenium status with insulin resistance was also examined [ 6 , 89 , 90 ]. Several types of research observational and analytical studies have been used to estimate selenium safe dose and the risk of T2DM, each with its advantages and limitations [ 91 , 92 ].…”
Section: Introductionmentioning
confidence: 99%
“…As conflicting results have been reported regarding the association of selenium with diabetes mellitus meta-analysis was applied to develop a more correct estimate of the effects’ magnitude [ 28 , 31 , 90 , 93 , 94 ]. That study design reduces bias and produces more reliable findings [ 95 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation